Vibrant Architecture. Matter as a CoDesigner of Living Structures (2015)
This chapter explores how vibrant matter may be applied within an urban context through the design and construction of webs of living materials that constitute complex fabrics, such as our soils, which may be synthetically produced within underused and under-imagined spaces within our home and cities (see Fig. 12.1). The careful design and engineering of these fabrics may provide designers with access to a new kind of production platform that may not only change our design practices but also shape new cultural values. Potentially, these post-natural fabrics may offer a fertile field of new possibilities, which may give rise to vibrant cities where human and non-human communities collaborate and codesign our living spaces and evolve alongside us as expressions of Millennial Nature.